Quantum chemical studies on radical cation clusters and X-ray emission spectroscopy - Wadey, Jack D. (2014)
This thesis presents computational studies of two main projects, the first concerning the structure and bonding of mixed component radical cation clusters and the second relating to quantum chemical calculations of X-ray emission spectroscopy. Basin hopping in conjunction with second order Møller-Plesset perturbation theory is used to characterise the lowest energy isomers of mixed component radical cation clusters of the form [H2O-X]•+, [(H2O)2-X]•+ and [H2O-X2]•+, where X=PH3, H2S and HCl, with the relative energies refined using coupled cluster theory calculations. For the dimers where X=H2S or HCl, a proton transfer based structure comprising H3O+ and SH• or Cl• radicals has the lowest energy structure whereas for X=PH3 a hemibonded structure is most stable. For the trimers, a much wider range of possible isomers based upon both proton transfer and hemibonded structures are observed. The calculation of X-ray emission spectroscopy with equation of motion coupled cluster theory (EOM-CCSD), time dependent density functional theory (TDDFT) and resolution of the identity single excitation configuration interaction with second order perturbation theory (RI-CIS(D)) is studied. TDDFT with standard exchange- correlation functionals predicts transition energies that are much larger than exper- iment. Optimisation of a hybrid and short-range corrected functional to predict the X-ray emission transitions results in much closer agreement with EOM-CCSD. The most accurate exchange-correlation functional identified is a modified B3LYP hybrid functional with 66% Hartree-Fock exchange, denoted B66LYP, which predicts X-ray emission spectra for a range of molecules including fluorobenzene, nitrobenzene, acetone, dimethyl sulfoxide and CF3Cl in good agreement with experiment.